The Politics of Criminal Law on The Protection of Rape Victims Based on the Qanun of Jinayah in Aceh - Muhammad Nur; Muhammad Salda; Hamdani Hamdani (Universitas Syiah Kuala, 2021)
A country must protect its citizens, including the rape victims. Unfortunately, the protection is not clearly regulated in the form of restitution and compensation in the Criminal Code (KUHP) and Law Procedures Code (KUHAP). The issuance of Qanun Number 6 the Year 2014 about Jinayah Law has contributed significant changes and progress to the protection of rape victims. The study focused on how the politics of criminal law protects rape victims based on the Qanun of Jinayah law in Aceh. The research applied the normative juridical method, specifically analytical descriptive research. The data sources were primary and secondary legal sources. The data analysis was conducted qualitatively. The result indicated that there are two types of protection in the politics of criminal law on the protection of rape victims based on the qanun of jinayah law. First, the ta'zir penalty or fines in the form of gold to the perpetrators. Second, the payment of uqubat restitution from the perpetrators to the rape victims, a maximum of 750 grams of pure gold.